Woman: An intimate geography - Angier, Natalie (Anchor Books, 2000)
Woman is a fascinating, fact-filled guide that covers everything from organs to orgasms, hormones to hysterectomies. With her characteristic clarity, insight, and sheer exuberance of language, bestselling author Natalie Angier cuts through the still-prevalent myths and misinformation surrounding the female body, that most enigmatic of evolutionary masterpieces. With a witty and assured narrative, and a reader-friendly dose of science, Woman is an essential and engaging resource for all time.
Keywords: amériques; approches et analyses; biologie; corps; différence des sexes; discipline; fem1000; médecine; premier cycle; psychologie; rapports sociaux de sexe; régions géographiques; santé; sciences; sciences humaines; stéréotypes; thématiques; états-unis

Manifesta young women, feminism, and the future - Baumgardner, Jennifer (1970- ).; Richards, Amy (Farrar, Straus and Giroux, 2000)
In the year 2000, girl culture was clearly ascendant. From Lilith Fair to Buffy the Vampire Slayer to the WNBA, it seemed that female pride was the order of the day. Yet feminism was also at a crossroads; "girl power" feminists were obsessed with personal empowerment at the expense of politics, while political institutions such as Ms. and NOW had lost their ability to speak to a new generation. In Manifesta, Jennifer Baumgardner and Amy Richards brilliantly revealed the snags in each feminist hub, all the while proving that these snags had not imperiled the future of the feminist cause. The book went on to inspire a new generation of female readers, and has become a classic of contemporary feminist literature.
Keywords: 1900-1999; 1990-1999; amériques; fem1000; militance; mouvements féministes; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis; études culturelles

Debora et Judith : l’amour entre femmes dans l’église catholique. Et CIEL parlait, ce serait l’ENFER? - Bazinet, Colette (Recherches féministes, 2000)
Keywords: amériques; approches et analyses; compte-rendu; discipline; fem1000; invisibilités; lesbianisme; premier cycle; québec; ressource en ligne; régions géographiques; science des religions; sciences humaines; sexualité; thématiques; église

Le siècle dans la tourmente du féminisme - Daigle, Johanne (Globe : revue internationale d’études québécoises, 2000)
L’empreinte du féminisme sur le XXe siècle québécois est indélébile. De l’aube au crépuscule du siècle, la « question des femmes » a coloré les grands débats, imprégné les luttes socio-politiques et laissé sa marque sur les systèmes de lois, les institutions, l’organisation du travail et les modes de vie. Cet article veut montrer comment, dans une perspective historique, la « question des femmes » — ainsi posée par les élites masculines — fut pressentie comme l’une des grandes interrogations de ce siècle et comment les changements survenus dans la reconfiguration des rapports entre hommes et femmes — des identités sexuelles aux modèles qui les supportent — restent au coeur des enjeux d’une société.
https://www.erudit.org/en/journals/globe/2000-v3-n2-globe1497493/1000582ar/
Keywords: 1900-1999; EDI; amériques; approches et analyses; conflit; discipline; discours dominant; droits des femmes*; fem1000; histoire; histoire et politique; inégalités; militance; patriarcat; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppression; thématiques; travail; épistémologie

Genders - Glover, David; Kaplan, Cora (Routledge, 2000)
"Gender" has, in recent years, become one of the busiest terms in literary and cultural theory, as well as being one of the most contested. David Glover and Cora Kaplan chart the main lines of contemporary debate surrounding gender in a guide which:* presents a history of the term, from the sexology of psychoanalysis of the 1960s to its current usage within the interdisciplinary field of gender studies* looks at the major perspectives on gender from second-wave feminist writers and critics* examines new work on masculinity in literary and cultural studies* assesses how the creation of new queer and gendered identities has impacted the study of literature* surveys empirical and theoretical work on readership and spectatorship, looking in detail at modes of fantasy, cultural consumption, reader response and fan cultures.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000-2029; amériques; antiféminisme; approches et analyses; arts; culture populaire; discipline; fem1000; littérature; masculinisme; premier cycle; périodes historiques; queer; ressource en ligne; régions géographiques; états-unis; études culturelles; études littéraires

Expériences des femmes et théologie. La théologie « mujerista » : une nouvelle pratique théologique - Melançon, Louise (Laval théologique et philosophique, 2000)
Les théologies féministes sont plurielles de par la diversité des expériences qui leur donnent naissance. S'il est vrai que l'expérience du sexisme et de l'androcentrisme traverse les discours féministes, elle n 'en est pas moins contextuelle. La prise en compte de ces expériences des femmes en théologie interroge et commence à modifier la pratique même de la théologie. La théologie mujerista née de la survie des femmes hispano-américaines en est un exemple remarquable.
Keywords: amérique latine; amériques; approches et analyses; discipline; fem1000; femmes*; intersectionnalité; inégalités; premier cycle; ressource en ligne; régions géographiques; science des religions; sciences humaines; sexisme; systèmes d'oppression; théologie; états-unis